PENILAIAN TINGKAT KESEHATAN KOPERASI (STUDI KASUS PADA KOPERASI KREDIT SAMAMORA KELURAHAN TAUBNENO KECAMATAN KOTA SOE KABUPATEN TIMOR TENGAH SELATAN) - Ribka A. Liunokas; Petrus E. de Rozari; Wehelmina M. Ndoen (Universitas Nusa Cendana, 2017)
This study aims to investigate the healthy level of the Credit Cooperative Samamora in TaubnenoDistricts, Soe City, South Central Timor Regency, and its development in 2012-2016 in terms ofSeven Aspects i.e Capital, Assets Quality, Management, Efficiency, Liquidity, Autonomy andGrowth, and Self-Identity. This was an descriptive study, in which the object was the Healthy ofCredit Cooperative Samamora in 2012-2016. The data analysis was case study approach referringto Regulations of the State Minister of Cooperative and Small and Medium Scale Enterprises No.14/Per/M.KUKM/XII//2009 about an evaluation of the healthy level of the cooperative.. Theresult indicated that Credit Cooperative Samamora in 2012-2016 : (1) The aspect of Capital was inthe moderate healthy level. (2) The aspect of Quality of Productive Assets was in the moderatehealthy level. (3) The aspect of Management was in the moderate healthy level. (4) The aspect ofEfficiency was in the moderate healthy level. (5) The aspect of Liquidity which was in the ratherunhealthy level. (6) The aspect of Autonomy and Growth was in the the unhealthy level. (7) Theaspect of Self-Identity was in the moderate healthy category. The progress of healthy level at CreditCooperative Samamora in 2012-2016 experienced fluctuation. In 2012,2013 and 2015 CreditCooperative Samamora was in the moderately healthy and in 2014 and 2016 was in the unhealthylevel, with average score obtained is 60,80 which was moderate healthy category.Keywords : Cooperative, Health Level